USING TOURISM BROCHURES IN TEACHING WRITING DESCRIPTIVE TEXT TO IMPROVE THE WRITING ACHIEVEMENT OF THE EIGHTH GRADE STUDENTS AT SMP KARYA IBU PALEMBANG - Regy Amelia; Desi Surayatika (Universitas Indo Global Mandiri, 2016)
This study aimed at seeing whether the use of tourism brochures was effective to improve students’ achievement in writing descriptive text. In particular, it sought to find out whether tourism brochures was an effective means for generating ideas in writing descriptive text. The design selected for this study was a quasi-experimental study using nonequivalent pretest posttest design. The population of the study was all eighth grade students at SMP Karya Ibu Palembang. This study involved 262 students of the eighth graders. The sample was purposively chosen as the sample of the study in which 20 students belonged to the experimental group and 20 students belonged to the control group. The data were obtained by means of writing test as the instruments. The study lasted one and half months in that during the treatment, the student were exposed to a wide range of writing activities including process writing particularly a prewriting activity by using tourism brochures. The result shows that there was a significant difference among the writing test mean scores before and after they were exposed to tourism brochures and there was a significant difference in students’ test scores between the students who were taught by tourism brochures and those who were not. The research findings revealed that the use of tourism brochures was effective to improve students’ writing achievement. These findings were also supported by the significant improvement in writing achievement between the two groups in terms of the six aspects of writing (topic sentence, supporting detail sentence, concluding sentence, word choice, mechanics and grammar, sensory details). The results of the pre-test and post-test showed a positive response that tourism brochures was very helpful for the students in improving their descriptive writing achievement especially in generating, gathering, exploring and organizing their ideas prior to writing a descriptive text. The study was expected to yield a better quality of writing and build writing habit among students in a greater scale.Key Word: Writing achievement, Tourism brochures, Descriptive text